2020
DOI: 10.3390/ijms21249699
|View full text |Cite
|
Sign up to set email alerts
|

Yeast Microbiota during Sauerkraut Fermentation and Its Characteristics

Abstract: Sauerkraut is the most important fermented vegetable obtained in Europe. It is produced traditionally by spontaneous fermentation of cabbage. The aim of this study was to determine biodiversity of yeasts present during fermentation of eight varieties of cabbages (Ambrosia, Avak, Cabton, Galaxy, Jaguar, Kamienna Głowa, Manama and Ramco), as well as characterize obtained yeast isolates. WL Nutrient Agar with Chloramphenicol was used to enumerate yeast. Isolates were differentiated using RAPD-PCR and identified b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 38 publications
2
19
0
Order By: Relevance
“…As for organic acids, the increasing content of oxalic acid in dried–fermented radishes might be produced and accumulated via the glycolytic pathway followed by the TCA cycle (Satora et al., 2020). Furthermore, the growing content of succinic acid, as well as malic acid, was detected in the spontaneously dried–fermented radishes, and their synthesis was related to the transition among organic acids in the TCA cycle (Zou et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…As for organic acids, the increasing content of oxalic acid in dried–fermented radishes might be produced and accumulated via the glycolytic pathway followed by the TCA cycle (Satora et al., 2020). Furthermore, the growing content of succinic acid, as well as malic acid, was detected in the spontaneously dried–fermented radishes, and their synthesis was related to the transition among organic acids in the TCA cycle (Zou et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Our results found no significant difference in fungal communities between groups, except for the differential abundance of some fungi in some consumers only, including R. mucilaginosa. This oleaginous microorganism and common environmental yeast has been identified in a number of indigenous fermented foods including cocoa, kefir (Menezes et al, 2020), Chinese rice wine (Wu et al, 2013), other fermented milks, and sauerkraut (Satora et al, 2020). Along these lines, we recently showed that faecal fungal communities across different primate species are highly influenced by diet and environment (Sharma et al, 2022), which is in accordance with previous studies showing the strong influence of diet on the mycobiome of mice and non-human primates (Sun et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Its appeal lies not only in its gustatory allure but also in its nutritional prowess, serving as a rich reservoir of probiotics and vitamins [42,43]. Despite its virtues, sauerkraut's elevated sodium content may warrant caution among individuals susceptible to hypertensive disorders or sodium-induced complications [44]. The preparation of sauerkraut entails a minimalist approach, involving the maceration of shredded cabbage with a judicious amount of salt to incite the process of lacto-fermentation.…”
Section: Introductionmentioning
confidence: 99%
“…As the cabbage releases its natural juices and undergoes enzymatic breakdown, it becomes submerged in a brine solution, impeding the proliferation of spoilage microorganisms while fostering the growth of lactic acid bacteria. This transformative journey unfolds over the course of 1-4 weeks at ambient temperatures, culminating in a tangy, probiotic-rich condiment that embodies the essence of traditional fermentation practices [44,45]. The preparation of sauerkraut entails a minimalist approach, beginning with the selection of fresh cabbage.…”
Section: Introductionmentioning
confidence: 99%